2014
DOI: 10.1016/j.biomaterials.2014.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Heparin–chitosan nanoparticle functionalization of porous poly(ethylene glycol) hydrogels for localized lentivirus delivery of angiogenic factors

Abstract: Hydrogels have been extensively used for regenerative medicine strategies given their tailorable mechanical and chemical properties. Gene delivery represents a promising strategy by which to enhance the bioactivity of the hydrogels, though the efficiency and localization of gene transfer have been challenging. Here, we functionalized porous poly(ethylene glycol) hydrogels with heparin-chitosan nanoparticles to retain the vectors locally and enhance lentivirus delivery while minimizing changes to hydrogel archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Nanoparticles constructed with heparin have been studied as cytokine delivery carriers for years because many cytokines, such as stromal SDF-1, BMP-2, vascular endothelial growth factor, placental growth factor, platelet-derived growth factor, and fibroblast growth factor, [29][30][31][32][33] can bind to heparin through their conserved amino acid sequences. The use of chitosan and heparin for the delivery of bioactive molecules has many advantages, including being inexpensive, biodegradable, noncytotoxic, nonimmunogenic, 34,35 easy to process, absorbable, and having safe degradation end product. 36,37 Our previous study about CSO/H NPs showed that they are stable in physiological pH solution and exhibited improved biocompatibility of chitosan-based nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles constructed with heparin have been studied as cytokine delivery carriers for years because many cytokines, such as stromal SDF-1, BMP-2, vascular endothelial growth factor, placental growth factor, platelet-derived growth factor, and fibroblast growth factor, [29][30][31][32][33] can bind to heparin through their conserved amino acid sequences. The use of chitosan and heparin for the delivery of bioactive molecules has many advantages, including being inexpensive, biodegradable, noncytotoxic, nonimmunogenic, 34,35 easy to process, absorbable, and having safe degradation end product. 36,37 Our previous study about CSO/H NPs showed that they are stable in physiological pH solution and exhibited improved biocompatibility of chitosan-based nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, virus particles were incorporated in heparinchitosan nanoparticles, which were finally immobilized onto a PEG porous structure. Interestingly, an increase of endothelial cells and blood vessels around the hydrogel used was observed using both in vitro and in vivo approaches (118) .…”
Section: Hydrogels For Angiogenesismentioning
confidence: 99%
“…The most likely explanation is the interaction between the positively-charged chitosan and negatively-charged bacterial membrane leading to the leakage of cellular proteins and other intracellular constituents. Chitosan can also enhance the binding and retention of lentiviruses, prolonging and enhancing transgene expression within a PEG hydrogel scaffold [25]. A major drawback of chitosan in tissue engineering is its poor solubility in neutral aqueous solutions and organic solvents due to the presence of amino groups and its high crystallinity [26]; therefore, the modification of chitosan is necessary to expand its applications.…”
Section: Biomaterials Used As Injectable Scaffoldsmentioning
confidence: 99%